Children's Care, Learning & Development - Beith, Kate. (Harlow : Heinemann, 2008)
Written by the authors of the bestselling S/NVQ Early Years Care and Education resources, this candidate handbook contains everything students need to succeed in the S/NVQ children's care, learning and development, level 2.
Previous ed.: Oxford: Heinemann Educational, 2005.
Includes index.
Keywords: Child care -- Great Britain; Child development -- Great Britain; Early childhood education -- Great Britain; Child care -- Law and legislation -- Great Britain; Child development -- Law and legislation -- Great Britain; Early childhood education -- Law and legislation -- Great Britain; Society